The impact of animated karaoke on vocabulary acquisition among Japanese language learners in Malaysian universities - Abdullah, Muhammad Alif Redzuan; Hussin, Sanimah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
This research paper aimed to explore and investigate whether the use of animated karaoke in the Japanese language classes has an influence on vocabulary acquisition among Malaysian Japanese language learners. The study was conducted on 100 students learning the Japanese language at the beginner level as an elective subject at the Faculty of Modern Languages and Communication, Universiti Putra Malaysia (UPM). Data were collected through questionnaires, interviews, and observations. The analytical descriptive result showed that the participants were able to memorize and understand Japanese vocabulary quickly and easily after watching animation consisting of visual graphics combined with text which stimulate their brain. Data from the interviews also showed that the target vocabulary items were pronounced accurately and correctly when learners sang along while watching the animated karaoke. The triangulation of data showed that animated karaoke is a good tool to engage participants in learning the Japanese language while at the same time, having fun and feeling highly motivated to explore the language. The implication of the study suggests that the use of animated karaoke in other foreign language classes will help boost students’ confidence and motivation level.